Peran Perceived Social Support terhadap Intolerance of Uncertainty pada Dewasa Muda - Shannon Jieling Kurniawan; Sri Tiatri (YASIN, 2026)
Emerging adulthood is a developmental phase spanning ages 18–25 that is characterized by major transitions in education, career, and interpersonal relationships, during which individuals often experience a “feeling in-between” state—no longer adolescents yet not fully established as adults. High demands for exploration and life instability in this phase render emerging adults vulnerable to mental health problems, one of which is intolerance of uncertainty. This study aimed to examine whether perceived social support plays a role in intolerance of uncertainty among emerging adults. A quantitative method with a correlational approach was employed using simple linear regression analysis. The participants were 163 males and females aged 18–25 years residing in the Jabodetabek area. The instruments used were the Intolerance of Uncertainty Scale–12 and the Multidimensional Scale of Perceived Social Support. The findings indicated a positive role of perceived social support in intolerance of uncertainty among emerging adults (r = .245; p < .05), with a contribution of 6%, meaning that the higher the level of perceived social support experienced by individuals, the higher their intolerance of uncertainty. This result is inconsistent with previous studies reporting a negative role of perceived social support in intolerance of uncertainty, but aligns with other findings indicating that perceived social support exerts limited influence on intolerance of uncertainty. Overall, this study provides empirical insights into the dynamics of the relationship between perceived social support and intolerance of uncertainty among emerging adults in urban areas of Indonesia and underscores the need to consider contextual factors when interpreting the role of social support in mental health.